2014
DOI: 10.1523/jneurosci.0933-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Switch of Leptin Signaling in Arcuate Nucleus Neurons

Abstract: Leptin is well known for its role in the regulation of energy homeostasis in adults, a mechanism that at least partially results from the inhibition of the activity of NPY/AgRP/GABA neurons (NAG) in the arcuate nucleus of the hypothalamus (ARH). During early postnatal development in the rodent, leptin promotes axonal outgrowth from ARH neurons, and preautonomic NAG neurons are particularly responsive to leptin's trophic effects. To begin to understand how leptin could simultaneously promote axonal outgrowth fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 48 publications
7
90
1
Order By: Relevance
“…As expected, leptin treatment caused a marked increase in pSTAT3 staining in the ARH of control pups on P10 ( Figure 5C). However, the same leptin treatment resulted in significantly fewer numbers of pSTAT3-IR cells in the ARH of P10 neonates chroni- different neurophysiological effects in neonates versus adults, a recent study from Baquero and colleagues reported that during the preweaning period leptin exerts stimulatory electrophysiological effects on NPY/AgRP neurons although it inhibits those same neurons at weaning and in adults (34). Notably, we found that ghrelin influences development of projections to both the neuroendocrine and preautonomic compartments of the PVH.…”
Section: G and H)supporting
confidence: 48%
“…As expected, leptin treatment caused a marked increase in pSTAT3 staining in the ARH of control pups on P10 ( Figure 5C). However, the same leptin treatment resulted in significantly fewer numbers of pSTAT3-IR cells in the ARH of P10 neonates chroni- different neurophysiological effects in neonates versus adults, a recent study from Baquero and colleagues reported that during the preweaning period leptin exerts stimulatory electrophysiological effects on NPY/AgRP neurons although it inhibits those same neurons at weaning and in adults (34). Notably, we found that ghrelin influences development of projections to both the neuroendocrine and preautonomic compartments of the PVH.…”
Section: G and H)supporting
confidence: 48%
“…The mechanisms underlying the opposing effects of leptin on hypothalamic and hindbrain axon growth remain to be investigated. However, recent data have suggested that the transition from stimulatory to inhibitory effects of leptin on neuronal activity occurs in parallel with the acquisition of functional ATP-sensitive potassium channels (Baquero et al, 2014), and these data support the hypothesis that leptin activates distinct membrane-linked and intracellular pathways in hindbrain and hypothalamic neurons during development. Prenatal leptin exposure could also result in changes in insulin levels that could then, in turn, indirectly affect the autonomic innervation of the pancreas.…”
Section: Discussionmentioning
confidence: 59%
“…These findings are similar to those in the rat, where co-localization with glutamic acid decarboxylase, a rate-limiting enzyme for GABA production, identified at least one-quarter of GABA neurons express NPY [48] . There is long-standing functional and anatomical evidence that ARN NPY neurons use GABA neurotransmission in the regulation of circuits mediating food intake behavior [49] , and more recent approaches suggest that co-released GABA actions at postsynaptic targets are essential for normal feeding behavior [3,4,50] . Although the co-expression of GABA in virtually all NPY neurons is well accepted, the present study defines, for the first time, the specific proportion of ARN GABA neurons that co-localize and presumably co-release NPY in the mouse.…”
Section: Discussionmentioning
confidence: 99%